Pendapat Penegak Hukum Terhadap Pemidanaan Penyelenggara Jalan Di Kota Padangsidimpuan ditinjau Menurut Hukum Pidan Islam - Harahap, Efnilasari (Jurnal El-Thawalib, 2022)
Road operators are activities that include the regulation, financing, construction and supervision of roads, planning policy formulation activities, drafting, general planning, and drafting road laws and regulations, carried out by the authorities aimed at realizing order and legal certainty in road operators, realizing the role of the community in road operators and realizing the role of road operators and optimally providing services to road operators  community. The formulation of the problem from this study is how the law enforcement opinions of the city of Padangsidimpuan towards the punishment of road operators and how the review of Islamic criminal law on the punishment of road operators. The purpose of this study is to find out the opinion of padangsidimpuan city law enforcement towards the punishment of road operators and to find out the review of Islamic criminal law on the punishment of road operators. The theory used in this study is a theory related to the punishment of road operators and Law No. 22 of 2009 concerning Road Traffic and Transportation. furthermore, the type of research used is field research (field research) using qualitative analysis with deductive methods. The results of the research obtained were that the punishment of belun road operators was carried out in the city of Padangsidimpuan due to public ignorance regarding the existence of Law No. 22 of 2009 concerning Road Traffic and Transportation and the factors that influenced the non-implementation of article 273 of Law No. 22 of 2009 concerning Road Traffic and Transportation was the lack of socialization of the Law to the Community.